Professional behaviours and factors contributing to nursing professionalism among nurse managers. (30th October 2014) - Tanaka, Michiko; Taketomi, Kikuko; Yonemitsu, Yoshikazu; Kawamoto, Rieko
Abstract : Aim: To examine the perception of professional behaviours and factors contributing to nursing professionalism among nurse managers. Background: Professional behaviours influence nursing professionalisation and managers' behaviours strongly impact professional development. In Japan, few studies have examined professional nursing behaviours from the nurse managers' perspective. Methods: The Behavioural Inventory for Professionalism in Nursing was performed with 525 nurse managers representing 15 facilities in Japan. Results: The highest professional behaviours score obtained was 'competence and continuing education' and the lowest behavioural score was 'publication and communication'. The results demonstrate that higher nursing professionalism is related significantly to the increased length of nursing experience, a higher level of educational preparation and the current position as a nurse administrator. Conclusion: This study demonstrated that nursing professionalism is influenced by years of experience and nursing management education. Implications for nursing management: Awareness of extrinsic professional factors is important continually to maintain nursing professionalism. The findings of our study may help nurse managers to continue their self‐development and to realise the potential of their nursing staff by developing professionalism. These findings also provide an understanding of international professionalism trends to achieve higher levels of nursing professionalism through the evaluation of professional nursing behaviours.